Management of the Natural Environment in the Perspective of ‘Public Governance’ - Korporowicz-Żmichowska, Violetta (Studia Ecologiae et Bioethicae, 2021)
Natural environmental management is the activity of society, organisations, and individuals, aimed at limiting unfavourable changes in eco-systems. This management is the process of making and implementing decisions, regarding the state of the environment. Moreover, it is a practical activity, aimed at maintaining and improving the condition of the natural environment, which is being degraded as a result of the economic and living activities of man. Environmental management must be consistent with the state's ecological policy, which is a deliberate and conscious set of activities of state authorities. The purpose behind this policy is to ensure ecological safety for all citizens. Environmental policy is about top-down decisions, plans that are created to improve the common good, which is the environment. This improvement concerns the environment and its quality, which is not only a ‘private good’. It is also a public good, as it is of particular importance for the functioning of a given society. Some of the problems related to environmental protection, can be solved by implementing new organisational solutions, treated as a social process. We are talking about the idea of ‘public governance’, which is a bottom-up approach to management in the public sphere, including environmental management. ‘Public governance’ or ‘participatory public management’ is a type of management that is characterised by: stakeholder involvement, transparency of decisions, equality, and the lack of exclusion of individual members or groups of society, from the possibility of deciding on the shape of public services. An example here may be civic budgets, which enable local communities to co-decide on the implementation of investments, financed from a part of the local government budget. The aim of the article, meanwhile, is to present ‘public governance’ - one of the concepts of management in the public sector, and to try to answer whether the concept of public governance can be used in managing the natural environment.